DENTAL SERVICES MARKETING IN PRACTICES - Daryono; Wirawan Dony Dahana; Yuary Farradia (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Introduction: The rapid development and change in the digital world has had a big impact on the world of dentistry. Digital marketing is very good in the process of doing marketing management that can be applied to the intention of visiting dental care to dental clinics. Objective: To find out the digital marketing strategy in daily dental services. Method: The method of searching for articles on digital marketing strategies for dental services in dental clinics in electronic databases is Semantic Scholar. The total initial search results in the database totaled 1000 articles using the keyword "Dental Services Marketing". Furthermore, the inclusion and exclusion criteria were determined and adjusted to the population analysis, concept and context. Result: A total of 1000 articles were identified and screened and duplications were removed, resulting in 10 articles that met the inclusion criteria. Conclusion: Digital marketing strategy in dentistry is an approach used to promote services and increase patient trust through digital platforms. Some of the strategies applied are content seeding, influencer marketing, social media, website, google maps optimization, hiring a digital marketing agency and education. In the application of digital intelligence (business intelligence) in strategic management for dentistry and dental clinics that can be useful such as Digital Strategic Management, Telehealth Services, Data analytics for treatment plans, Utilizing Digital Information, Automating Administrative Duties, Utilizing Digital Imaging and Diagnostic Technologies, Feedback Mechanisms and improving and promoting patients about oral health both treatment and prevention.